HUKUM ANGKUTAN UMUM ILEGAL BAGI PENUMPANG BILA TERJADI KECELAKAAN - Putra, Reza Adi; Saputra, Arikha (Universitas Muhammadiyah Ponorogo, 2023)
ABSTRACTTransportation has now become a basic human need in fulfilling its mobility. The government is trying to make this happen by building mass public transportation such as bus rapid transit or BRT, city transportation and online-based transportation. However, it seems that it is still unable to meet the needs of various communities so that illegal public transportation or dark travel with private vehicles with black plates does not meet the requirements for public transportation, so that if an accident occurs it will be weak in the field of legal regulations as stipulated in Law Number 22 of 2009 concerning Traffic and road transport. The author conducted research using normative juridical methods guided by applicable laws and regulations, as well as using analytical descriptive methods to find out and understand the object of study. Illegal public transportation or dark travel operates without a permit to transport passengers without life insurance protection and does not pay mandatory fees as stipulated in Law Number 33 of 1964 concerning Passenger Accident Compulsory Insurance Funds, so that if an accident occurs the legal consequences are weak because they will not receive compensation. loss, if the passenger dies or suffers permanent disability. The government is responsible for organizing public transportation in an effort to meet the need for safe, secure, comfortable and affordable transportation. So public transportation must be in the form of a company that is licensed, legal entity and is required to pay mandatory contributions for life insurance for passengers, if an accident occurs they will receive compensation. Public transportation is illegal if in the event of an accident it will not get compensation due to death and permanent disability, because it does not pay mandatory coverage. As a result, passengers only receive compensation from the vehicle owner.